The Biopsychosocial Impact of COVID-19 on Older Adults. (7th September 2021) - Laher, Nazeefah; Bocchinfuso, Sara; Chidiac, Madeline; Doherty, Claire; Persson, Alexandra; Warren, Emma
COVID-19 has spread rapidly around the world and taken over 2.6 million lives. Older adults experience disproportionate morbidity and mortality from the disease because increasing age and the presence of comorbidities are important predictors of negative outcomes. Lasting effects of COVID-19 have been described after recovery from the acute illness despite eradication of the virus from the body. The impact of COVID-19 on a person's biological health post-infection is observed in multiple systems including respiratory, cardiac, renal, haematological, and neurological. Psychological dysfunction following recovery is also prevalent. Social factors such as distancing and stay at home measures leave older adults isolated and food insecure; they also face intertwined financial and health risks due to the resulting economic shutdown. This study examines the effects of COVID-19 on older adults using the biopsychosocial model framework.